Aspects of Morality and Behavior of Prosperous Families (Studies in the Pasia Nan Tigo Fishing Society) - Irmawita Irmawita; Fitri Dwi Arini; Ridha Husnul Hayati; Deni Putri Sartika (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
There is a unique stratification within the fishermen's society; the highest position is held by the owner of the ship, the middle position is tungganai (guardian), and the lowers is the crew (labor fishermen) and traditional fishermen. Poverty is on the lowers end. They struggle with difficulty to go out of their poverty. In terms of motivation, poor fishermen work hard to have a better life. However, their condition and situation do not give them a chance to escape poverty. This research uses an anthropological and cultural approach, concentrating on studying the understanding of morality and behavior of the fishermen community in Koto Tangah District, Padang City. The fishermen's community sees that the traditional work system in the research area has never made them live affluently. They are like digging a hole and live to close to the gap. They see this system as only benefiting the landlord because of the unfair resource distribution.